1997
DOI: 10.1136/hrt.78.3.273
|View full text |Cite
|
Sign up to set email alerts
|

Relation of serum cytokine concentrations to cardiovascular risk factors and coronary heart disease.

Abstract: Objective-To determine whether serum concentrations of the cytokines tumour necrosis factor a (TNFa) and interleukin 6 (IL-6), which regulate C reactive protein, are associated with cardiovascular risk factors and prevalent coronary heart disease. Design--A population based cross sectional study. Subjects and methods-198 men aged 50 to 69 years were part of a random population sample drawn from south London. Serum cytokine and C reactive protein concentrations were determined by enzyme linked immunosorbent ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
214
5
10

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(250 citation statements)
references
References 20 publications
18
214
5
10
Order By: Relevance
“…Previous studies have reported conflicting results about the relationship between IL-6 and HBP. 3,5,9,10,12,13,21,22 With one exception, 10 these studies were not designed to test the association between IL-6 and HBP, and failed to control for other cardiovascular risk factors. In fact, our results are consistent with those from the study of Chae et al, 10 the only other study in which appropriate control of confounding factors has been conducted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported conflicting results about the relationship between IL-6 and HBP. 3,5,9,10,12,13,21,22 With one exception, 10 these studies were not designed to test the association between IL-6 and HBP, and failed to control for other cardiovascular risk factors. In fact, our results are consistent with those from the study of Chae et al, 10 the only other study in which appropriate control of confounding factors has been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Some reports of studies in human subjects have shown a significant association between TNF-a and elevated BP, 11,12,21 but others have failed to show such an association. 13,14 Unfortunately, none of these studies has been designed to test this hypothesis and all have failed to control for other risk factors. However, in experimental studies the degree of activation of the TNF-a system has been positively and significantly associated with systolic and diastolic BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that the concentrations of TNF-␣ and other proinflammatory cytokines in peripheral blood are low. 48,49 Measurements are highly dependent on the sensitivity of the assays used, and some samples may fall below the limit of detection, mainly in healthy controls, as observed in our individuals.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with the role of human AT in the regulation of CRP levels. 11,12,14,34 In a random sample of 303 men aged 50 to 69 years, Mendall et al 34 had reported a significant association between the BMI and CRP levels. A significant relationship of CRP levels with the BMI was also noted among elderly men and women in the Cardiovascular Health Study.…”
Section: Discussionmentioning
confidence: 99%